챗봇 활용 수학 프로젝트 학습이 인공지능 리터러시에 미치는 영향 - 유희정; 고호경 (East Asian Mathematical Journal, 2023)
The purpose of this study is to investigate the impact of project learning using chatbots on artificial intelligence literacy. The subjects of the study were a total of 41 students from 1st to 3rd grade of general high school in Gyeonggi-do. Classes were held after school for a total of 6 hours, and the contents of the classes consisted of the concept and characteristics of artificial intelligence, the concept and expression of knowledge, OBT application for Kakao i open builder, guidance on how to create chatbots, and chatbot production practice. As a result of the pre- and post-test of the experimental group, the quantitative value of artificial intelligence literacy increased in all three grades. In the case of second-year students who set up a comparison group, when compared with the results of the comparison group, there was a significant positive effect on the AI literacy result, and female students were found to be more effective than male students.
Keywords: Chat-bot; Artificial Intelligent; AI literacy; Project based learning